Isolation and Characterisation of Mesenchymal Stem Cells from Rat Bone Marrow and the Endosteal Niche: A Comparative Study - Norhayati Yusop; Paul Battersby; Amr Alraies; Alastair J. Sloan; Ryan Moseley; Rachel J. Waddington (Stem Cells International)
Within bone, mesenchymal stromal cells (MSCs) exist within the bone marrow stroma (BM-MSC) and the endosteal niche, as cells lining compact bone (CB-MSCs). This study isolated and characterised heterogeneous MSC populations from each niche and subsequently investigated the effects of extensive cell expansion, analysing population doublings (PDs)/cellular senescence, colony-forming efficiencies (CFEs), MSC cell marker expression, and osteogenic/adipogenic differentiation. CB-MSCs and BM-MSCs demonstrated similar morphologies and PDs, reaching 100 PDs. Both populations exhibited consistent telomere lengths (12–17 kb), minimal senescence, and positive telomerase expression. CB-MSCs (PD15) had significantly lower CFEs than PD50. CB-MSCs and BM-MSCs both expressed MSC (CD73/CD90/CD105); embryonic (Nanog) and osteogenic markers (Runx2, osteocalcin) but no hematopoietic markers (CD45). CB-MSCs (PD15) strongly expressed Oct4 and p16INK4A. At early PDs, CB-MSCs possessed a strong osteogenic potency and low potency for adipogenesis, whilst BM-MSCs possessed greater overall bipotentiality for osteogenesis and adipogenesis. At PD50, CB-MSCs demonstrated reduced potency for both osteogenesis and adipogenesis, compared to BM-MSCs at equivalent PDs. This study demonstrates similarities in proliferative and mesenchymal cell characteristics between CB-MSCs and BM-MSCs, but contrasting multipotentiality. Such findings support further comparisons of human CB-MSCs and BM-MSCs, facilitating selection of optimal MSC populations for regenerative medicine purposes.